2020
DOI: 10.1016/j.eururo.2020.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Online Visits in Urology During the COVID-19 Pandemic—Potential, Risk Factors, and Patients’ Perspective

Abstract: The main goals for urologists during the coronavirus disease 2019 (COVID-19) pandemic are to prevent their patients from getting COVID-19, protect themselves as health care professionals, and deliver optimal urology care [1]. While prioritisation strategies are being proposed [2,3], further measures are warranted for multifaceted action plans towards optimal perpetuation of urology care during the pandemic [4]. Urological telemedicine can lead to (1) fewer patient contacts, (2) lower infection rates among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 9 publications
2
146
0
6
Order By: Relevance
“…Elective surgeries have been suspended and even cancer cases have been postponed, with the hope that such delay will not have a negative impact on patient's outcome (9). Telemedicine has become an important tool, reducing the exposure of patients and clinicians, but only a small fragment of practitioners was prepared for this and most patients do not openly accept this new way modality of evaluation (10,11). As a result, urologists and other surgical specialists have been experiencing a tremendous impact on their income, especially those whose earnings are driven mostly from their private practice (12).…”
Section: Introductionmentioning
confidence: 99%
“…Elective surgeries have been suspended and even cancer cases have been postponed, with the hope that such delay will not have a negative impact on patient's outcome (9). Telemedicine has become an important tool, reducing the exposure of patients and clinicians, but only a small fragment of practitioners was prepared for this and most patients do not openly accept this new way modality of evaluation (10,11). As a result, urologists and other surgical specialists have been experiencing a tremendous impact on their income, especially those whose earnings are driven mostly from their private practice (12).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Larson et al demonstrated that telemedicine intervention in cancer patients is comparable with face-to-face interaction insofar as quality of life is concerned [16]. Thus, telemedicine appears to be a solution that offers contact-free continuity of care during the COVID-19 pandemic as well as any other crisis [17].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic situation is exceptional and generates enormous pressure on health systems. A drastic change from face-to-face visits to telemedicine occurred in urology as well as in other specialties (6,7). Depending on local regulations, telemedicine is a feasible option to triage patients, offering the advantages of reducing unnecessary hospital physical visits and the risk of transmission (3,8).…”
Section: Visits and Diagnosismentioning
confidence: 99%